2019
DOI: 10.1016/j.jtho.2019.08.1940
|View full text |Cite
|
Sign up to set email alerts
|

P2.17-29 Impact of Second Predominant Pattern on Recurrence in Early Stage Resected Lung Adenocarcinoma: A Multicentric Study

Abstract: resection was defined by free resection margins, but with less rigorous lymph node evaluation than systematic dissection and/or positivity of the highest mediastinal lymph node removed. Incomplete resection was defined by the presence of gorss or microscopic residual disease. Patient follow-up was updated until Jan/2019. Overall survival was analyzed by the Kaplan-Meier method, Log rank test and Cox proportional regression. Result: A total of 663 patients were identified. Mean age was 65.64 years, 338 men(50.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Regarding the investigation of the second predominant pathological subtype, Bertoglio et al ( 13 ) found the high-grade second predominant subtype was often associated with a poor prognosis as its proportion increased, while in an earlier study by Ito et al ( 14 ) evaluting the intermediate-grade dominant subtype, the lepidic subtype and nonlepidic subtype components could be used as factors for further grading and exhibited significance for prognoses. Furthermore, Bertoglio et al ( 15 ) found that as the second predominant subtype, the lepidic subtype had a better level of DFS, whereas the micropapillary type often predicted a poorer prognosis. Recently, Tsai et al ( 28 ) found no significant difference in DFS between the two groups, regardless of whether the second pathological subtype was invasive (acinar, papillary, micropapillary, and solid) or noninvasive (lepidic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the investigation of the second predominant pathological subtype, Bertoglio et al ( 13 ) found the high-grade second predominant subtype was often associated with a poor prognosis as its proportion increased, while in an earlier study by Ito et al ( 14 ) evaluting the intermediate-grade dominant subtype, the lepidic subtype and nonlepidic subtype components could be used as factors for further grading and exhibited significance for prognoses. Furthermore, Bertoglio et al ( 15 ) found that as the second predominant subtype, the lepidic subtype had a better level of DFS, whereas the micropapillary type often predicted a poorer prognosis. Recently, Tsai et al ( 28 ) found no significant difference in DFS between the two groups, regardless of whether the second pathological subtype was invasive (acinar, papillary, micropapillary, and solid) or noninvasive (lepidic).…”
Section: Discussionmentioning
confidence: 99%
“…The second predominant subtype was defined as the pathological subtype accounting for the second-largest percentage of lung adenocarcinoma. While the prognostic effects of the predominant pathological subtypes of LUAD have been confirmed (7)(8)(9)(10)(11)(12), the possible prognostic effects of the second predominant pathological subtypes have rarely been mentioned in the literature, and there are no consistent results among relevant studies (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%